Training Needs for Teachers in Jordan in Light of Modern Trends in Professional Development - AL-Momani, Mohammad Omar (2025)
The study aimed to identify the training needs of teachers in Jordan in light of modern trends in professional development. To achieve this goal, the researchers used the descriptive analytical approach by preparing a questionnaire to identify training needs, consisting of 39 statements, distributed over three main axes: the subjective aspect, the cognitive aspect and the performance aspect. The primary study sample consisted of 139 vocational education teachers. The study’s results concluded that the level of training needs in the performative and subjective aspects was high, the cognitive aspect was moderate, and the overall score for the fields was high, with an arithmetic mean of 3.76 and a standard deviation of 0.65. The domains were arranged according to their arithmetic averages, beginning with the performance aspect, then the subjective aspect, then the cognitive aspect. The study recommended the necessity of paying attention to training needs, which is the first step towards properly planning training programs for teachers.